Possession in Multiperspective: Perspectivism and Cross-Disciplinary Discussion of the Phenomenon of Possession - Saragih, Denni Boy (Sekolah Tinggi Teologi Trinity Parapat, 2024)
This paper explores the phenomenon of possession (kesurupan) from multiple perspectives, including theological, psychological, and cultural viewpoints. The study highlights how possession is understood and interpreted differently across various traditions, particularly within Indonesian culture. It examines the relationship between possession and spiritual beliefs, addressing both the communal and individual dimensions of the experience. The paper also delves into the psychological implications of possession, analyzing how mental health professionals approach cases of possession in contrast to religious practitioners. From a theological perspective, it is often interpreted as a demonic phenomenon, while empirical studies generally categorize it as a form of dissociative experience. By synthesizing these diverse perspectives, the paper aims to provide a synthetic understanding of possession, offering insights into its complex nature and the various factors that contribute to its manifestation. The study concludes with reflections on the implications for conversation between religious and psychological perspectives for Christian ministry in Indonesia.